A 10‐kV SiC‐MOSFET (Gen‐3) Half‐Bridge Module‐Based Isolated Bidirectional DC–DC Converter Block for Medium‐Voltage High‐Power Applications. Issue 1 (4th November 2020) - Acharya, Sayan; Anurag, Anup; Chattopadhyay, Ritwik; Rengarajan, Satish; Prabowo, Yos; Bhattacharya, Subhashish
Abstract : The packaging technology for the medium‐voltage silicon carbide (SiC)‐metal oxide semiconductor field‐effect transistor (MOSFETs) has come a long way since its inception. Now, it is feasible to design half‐bridge power modules based on 10‐kV SiC‐MOSFETs for higher current applications. This paves the way for many application areas for these devices, particularly for medium‐voltage and high‐power applications. This paper presents a design of a modular medium‐voltage, high‐power isolated DC–DC converter enabled by these 10‐kV SiC‐MOSFETs‐based power modules. The design objectives are targeted at increasing the efficiency, power density, and interoperability. The proposed DC–DC converter is aimed for applications like DC distribution for the data centers, subsea power transmission, offshore wind farms, and photovoltaic energy transmission–distribution–coordination; electric ship DC power transmission; solid‐state distribution transformer, etc. © 2020 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.